2010
DOI: 10.1021/jp9088244
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of F Elimination from Zeolitic D4R Units: A Periodic B3LYP Study on the Octadecasil Zeolite

Abstract: The mechanism of elimination of F -trapped inside the double four-membered ring (D4R) cages of octadecasil has been determined by means of periodic calculations at the B3LYP/VDZP//VTZP level of theory with the CRYSTAL06 program. Finite temperature and entropic effects are taken into account to study the efficiency of the elimination reaction, which is exothermic, requires acid media, and is catalyzed by cationic polar molecules with accessible protons, from which a hydronium ion has been considered in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…The energies of the transition states (O i migration barriers) have been obtained using the distinguished reaction coordinate technique following the method [30] as implemented in the CRYSTAL14 code. The optimized migration path corresponds to a trajectory of local minimum points on the potential energy surface (PES).…”
Section: Introductionmentioning
confidence: 99%
“…The energies of the transition states (O i migration barriers) have been obtained using the distinguished reaction coordinate technique following the method [30] as implemented in the CRYSTAL14 code. The optimized migration path corresponds to a trajectory of local minimum points on the potential energy surface (PES).…”
Section: Introductionmentioning
confidence: 99%
“…The nature of the transition point as saddle point has been confirmed by the vibrational analysis of the system which has evidenced the existence of one negative eigenvalue of the numerical Hessian matrix .…”
Section: Graphene/(0001) α‐Quartz Heterointerfacementioning
confidence: 78%
“…2b, which lies about 1.3 eV below the van der Waals minimum, a barrier of ∼ 2.25 eV has to be overcome. The nature of the transition point as saddle point has been confirmed by the vibrational analysis of the system which has evidenced the existence of one negative eigenvalue of the numerical Hessian matrix [50,51].…”
Section: Energy Landscape Of the Graphene/oterminated (0001)-␣-quartzmentioning
confidence: 97%
“…Double four-ring cages (d4r units, face symbol 4 6 , t-cub tile in the nomenclature of natural tilings 1 ) are a prototypical building unit of zeolites and zeotypes. A recent statistical analysis of the zeolite frameworks included in the IZA (International Zeolite Association) Database of Zeolite Structures 2 showed that the t-cub tile is the second most frequent tile, occurring in 36 out of 239 zeolite frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…Because the equilibrium Si-O-Si angle is closer to 150 degrees, 4,5 these building units are strained in all-silica zeolites. 6 The strain can be reduced through an incorporation of heteroatoms, especially germanium, at some corners of the cage, 4,7 or through encapsulation of fluoride anions inside the cages. 6 In fact, many all-silica zeolites containing d4r units have, so far, not been obtained in the absence of fluoride.…”
Section: Introductionmentioning
confidence: 99%